Wirtschaftspolitische Implikationen eines globalisierten Ordnungswettbewerbs aus evolutorischer Perspektive - Oliver Budzinski (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 1999)
– The process of globalization causes an increasing intensity of institutional competition, i.e. competition among national suppliers of institutional arrangements for mobile factors. This often leads to the conclusion that the competence of national economic policy actors is decreasing. As a consequence, economists often expect the emergence of more efficient institutions and a diminishing of discriminating interventions caused by lobbyism. Other scientists and politicians suspect a desocialization of the market economy and a regime of global companies. This paper inquires how and to what extent the hope for higher political efficiency and the fear of a race-to-the-bottom concerning standards is justified from the perspective of an evolutionary theory of competition (Hayek, Kerber). Therefore, a model of institutional competition as an institutional search- and discovery process is developped which generates situative institutional knowledge via the process of voice (elections, public opinion etc.) and the process of exit and entry of mobile factors looking for individual satisficing institutional arrangements. The results of the model consist of the fact, that a general decrease of the economic policy competence cannot be stated. There is no convergence to some optimal and efficient type of economic order, too. Instead, the challenges to economic policy change; a process that entails limits to policy competence as well as the emergence of new capabilities. This denies or at least reduces the fears concerning institutional competition. Yet, one cannot exclude the possibility of lobbyism in institutional competition, neither, although the powerful actors may change. Finally the discussion leads to the importance of an order of institutional competition since all processes of competition depend on their institutional conditions in producing the desired effects. This is a consequence of both the ordoliberal tradition and evolutionary economic theory.
Keywords: P0; K0; 330; Ordnungswettbewerb; evolutorische Ökonomik; Wirtschaftspolitik; institutioneller Wandel; Marktprozeßtheorie; Institutional competition and change; economic order; evolutionary econonomics; market process theory; economic policy